Asynchronous sampling terahertz time‐domain spectroscopy using semiconductor lasers. Issue 10 (1st May 2018) - Döpke, B.; Surkamp, N.; Hu, Y.; Brenner, C.; Klehr, A.; Knigge, A.; Tränkle, G.; Hofmann, M.R.
Abstract : Asynchronous optical sampling terahertz time‐domain spectroscopy using semiconductor laser‐based ultra‐short pulse sources is demonstrated. A pair of hybridly mode‐locked edge‐emitting external cavity lasers operating at a wavelength of 830 nm is used. Terahertz traces with spectral components over a range of 250 GHz are achieved.